Roads Out of Poverty? Assessing the Links between Aid, Public Investment, Growth, and Poverty Reduction - Agénor, Pierre-Richard (2012)
This paper presents a dynamic macroeconomic model that captures key linkages between foreign aid, public investment, growth, and poverty. Public capital is disaggregated into education, core infrastructure, and health. Dutch disease effects associated with aid are accounted for by endogenizing changes in the relative price of domestic goods. The impact of shocks on poverty is assessed through partial elasticities and household survey data. The model is calibrated for Ethiopia and changes in the level of nonfood aid are simulated. The amount by which (nonfood) aid should increase to reach the poverty targets of the Millennium Development Goals is also calculated, under alternative assumptions about the degree of efficiency of public investment.